Construct validity of the ovine model in endoscopic sinus surgery training. (8th September 2014) - Awad, Zaid; Taghi, Ali; Sethukumar, Priya; Tolley, Neil S.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To demonstrate construct validity of the ovine model as a tool for training in endoscopic sinus surgery (ESS). Study Design Prospective, cross‐sectional evaluation study. Methods Over 18 consecutive months, trainees and experts were evaluated in their ability to perform a range of tasks (based on previous face validation and descriptive studies conducted by the same group) relating to ESS on the sheep‐head model. Anonymized randomized video recordings of the above were assessed by two independent and blinded assessors. A validated assessment tool utilizing a five‐point Likert scale was employed. Construct validity was calculated by comparing scores across training levels and experts using mean and interquartile range of global and task‐specific scores. Subgroup analysis of the intermediate group ascertained previous experience. Nonparametric descriptive statistics were used, and analysis was carried out using SPSS version 21 (IBM, Armonk, NY). Results Reliability of the assessment tool was confirmed. The model discriminated well between different levels of expertise in global and task‐specific scores. A positive correlation was noted between year in training and both global and task‐specific scores (P < .001). Experience of the intermediate group was variable, and the number of ESS procedures performed under supervision had the highest impact on performance. Conclusions This study describes an alternative model for ESS training and assessment. It is also the first to demonstrate construct validity of the sheep‐head model for ESS training. Level of Evidence NA Laryngoscope, 125:539–543, 2015